2011
DOI: 10.1097/ana.0b013e3181ef2b11
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-induced Transient Asystole for Intracranial Aneurysm Surgery

Abstract: Adenosine cardiac arrest is a relatively novel method for decompression of intracranial aneurysms to facilitate clip application. With appropriate safety precautions, it is a reasonable alternative method when temporary clipping of proximal vessels is not desirable or not possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 10 publications
1
70
0
7
Order By: Relevance
“…In selected patients with giant aneurysms, deep hypothermia with circulatory arrest under cardiopulmonary extracorporeal circulation has been shown to be a feasible and possibly useful technique, but outcome data are lacking. [192][193][194][195][196] Transient cardiac pause induced by adenosine has been used to control bleeding from intraoperative aneurysm rupture or to decompress large aneurysms and facilitate aneurysm clip application 197,198 ; however, controlled studies are needed to validate this intervention.…”
Section: Anesthetic Management During Surgical and Endovascular Treatmentioning
confidence: 99%
“…In selected patients with giant aneurysms, deep hypothermia with circulatory arrest under cardiopulmonary extracorporeal circulation has been shown to be a feasible and possibly useful technique, but outcome data are lacking. [192][193][194][195][196] Transient cardiac pause induced by adenosine has been used to control bleeding from intraoperative aneurysm rupture or to decompress large aneurysms and facilitate aneurysm clip application 197,198 ; however, controlled studies are needed to validate this intervention.…”
Section: Anesthetic Management During Surgical and Endovascular Treatmentioning
confidence: 99%
“…No patient had any pulmonary side effects. The third case series, reported by Guinn et al, 15 included 27 patients whose aneurysms were primarily in the anterior circulation and whose surgeries where primarily elective. The individual adenosine dose range was 3 to 60 mg, and the total dose range was 3 to 285 mg.…”
Section: Adenosine-induced Transient Asystolementioning
confidence: 99%
“…In addition, adenosine can cause bronchoconstriction and therefore may be contraindicated for patients with asthma or chronic obstructive pulmonary disease. 14,15,[20][21][22][23] …”
Section: Disadvantages Complications and Contraindications Of Adenomentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the duration of hypotension, not necessarily asystole, was the single most important factor for adequate clip placement using this technique. 8 One serious complication during this study in one patient who experienced prolonged hypotension secondary to pulseless electrical activity required chemical intervention and cardiopulmonary resuscitation to reverse. The complication in this case was attributed to rapid redosing of adenosine without allowing for return of a normal hemodynamic profile between boluses.…”
Section: Adenosine-induced Cardiac Standstillmentioning
confidence: 99%